Unusual CO2 hydrate formation in porous media: Implications on geo-CO2 storage laboratory testing methods - Rehman, A.N. (Elsevier Ltd, 2022)
CO2 sequestration in geological sediments as hydrates is a promising technique currently being explored by research to permanently store CO2. To achieve this, studies on site selection and best experimental practices are useful to provide recommendations for understanding and implementing the process. In this study, the kinetics of CO2 hydrate formation was evaluated in quartz sand at 4 MPa and 274.15 K to gain insight on selecting a suitable location that provides high CO2 hydrate storage capacity. The study was conducted using a stainless-steel autoclave cell and a constant cooling method in pure water and brine system (3.3 wt NaCl). The study revealed that CO2 hydrate forms faster in quartz sand achieving about 87 CO2 to hydrate conversion in pure water as opposed to 55 CO2 to hydrate conversion in the brine system. The high hydrate conversion achieved in pure water is promising to provide a potential storage capacity of CO2 in sediments. However, visual confirmation revealed that a high percentage of the hydrates in the pure water system formed at the top of the sand bed within the reactor which is unusual and undesired for practical CO2 storage field applications. Interestingly, the hydrate formed in the brine system was within the porous media pore spaces. The results thus suggest that hydrate storage techniques experimental testing should be conducted in reactors with visual capabilities to gain a proper understanding of the location of the hydrates within the porous media. Â© 2021